Managing In- and Out-Migration of Health Workforce in Selected Countries in South East Asia Region - Viroj Tangcharoensathien; Phyllida Travis; Achmad Soebagjo Tancarino; Krisada Sawaengdee; Yanchen Chhoedon; Safeenaz Hassan; Nareerut Pudpong (Kerman University of Medical Sciences, 2018)
Background There is an increasing trend of international migration of health professionals from low- and middle- income countries to high-income countries as well as across middle-income countries. The WHO Global Code of Practice on the International Recruitment of Health Personnel was created to better address health workforce development and the ethical conduct of international recruitment. This study assessed policies and practices in 4 countries in South East Asia on managing the in- and out-migration of doctors and nurses to see whether the management has been in line with the WHO Global Code and has fostered health workforce development in the region; and draws lessons from these countries. Methods Following the second round of monitoring of the Global Code of Practice, a common protocol was developed for an in-depth analysis of (a) destination country policy instruments to ensure expatriate and local professional quality through licensing and equal practice, (b) source country collaboration to ensure the out-migrating professionals are equally treated by destination country systems. Documents on employment practice for local and expatriate health professionals were also reviewed and synthesized by the country authors, followed by a cross-country thematic analysis. Results Bhutan and the Maldives have limited local health workforce production capacities, while Indonesia and Thailand have sufficient capacities but are at risk of increased out-migration of nurses. All countries have mandatory licensing for local and foreign trained professionals. Legislation and employment rules and procedures are equally applied to domestic and expatriate professionals in all countries. Some countries apply mandatory renewal of professional licenses for local professionals that require continued professional development. Local language proficiency required by destination countries is the main barrier to foreign professionals gaining a license. The size of outmigration is unknown by these 4 countries, except in Indonesia where some formal agreements exist with other governments or private recruiters for which the size of outflows through these mechanisms can be captured. Conclusion Mandatory professional licensing, employment regulations and procedures are equally applied to domestic and foreign trained professionals, though local language requirements can be a barrier in gaining license. Source country policy to protect their out-migrating professionals by ensuring equal conditions of practice by destination countries is hampered by the fact that most out-migrating professionals leave voluntarily and are outside government to government agreements. This requires more international solidarity and collaboration between source and destination countries, for which the WHO Global Code is an essential and useful platform.